2021
DOI: 10.3390/gidisord3040018
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening: Have We Addressed Concerns and Needs of the Target Population?

Abstract: Despite the recognized benefits of colorectal cancer (CRC) screening, uptake is still suboptimal in many countries. In addressing this issue, one important element that has not received sufficient attention is population preference. Our review provides a comprehensive summary of the up-to-date evidence relative to this topic. Four OVID databases were searched: Ovid MEDLINE® ALL, Biological Abstracts, CAB Abstracts, and Global Health. Among the 742 articles generated, 154 full texts were selected for a more tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 155 publications
(489 reference statements)
1
10
0
Order By: Relevance
“…These evidences point to the need for effective interventions aimed at reducing disparities and improving access to care among more vulnerable individuals. In this regard, healthcare providers have both the power and responsibility to guide patients' decision-making processes and positively influence screening participation [32,33]. In accordance with a previous study on CRC conducted in Flanders [17] we have found that a higher percentage of people with at least one general practitioner (GP) visit in the previous year is associated with higher uptake of both CRC and BC screening.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These evidences point to the need for effective interventions aimed at reducing disparities and improving access to care among more vulnerable individuals. In this regard, healthcare providers have both the power and responsibility to guide patients' decision-making processes and positively influence screening participation [32,33]. In accordance with a previous study on CRC conducted in Flanders [17] we have found that a higher percentage of people with at least one general practitioner (GP) visit in the previous year is associated with higher uptake of both CRC and BC screening.…”
Section: Discussionsupporting
confidence: 77%
“…Higher education (as a proxy for education level and health literacy) may facilitate comprehension of screening information and, therefore, adhesion to preventive behaviors [27]. Moreover, with regard to FOBT screening, higher health literacy may help overcome psychological barriers related to stool collection [17,32]. Residential stability (same address), on the other hand, guarantees that invitation letters arrive at the correct address.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous research efforts are targeting a wider uptake of the CRC screening [ 5 ] through finding alternative, currently accepted, non-invasive screening methods [ 6 ] because CRC is still accountable for half of the cancer-related deaths worldwide [ 7 ]. Colonoscopy is both an exploratory and interventional procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, people who see their GP more regularly may overestimate their health status, feel "safer" and not feel the need to participate in screening. Nevertheless, literature shows that suggestions by one's GP may play an important role in positively influencing screening participation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Higher education (as a proxy for education level and health literacy) may facilitate comprehension of screening information and therefore adhesion to preventive behaviors [27]. Moreover, with regards to FOBT screening, a higher health literacy may help overcome psychological barriers related to stool collection [17], [33]. Residential stability (same address), on the other hand, guarantees that invitation letters arrive at the right address.…”
Section: Discussionmentioning
confidence: 99%